2005
DOI: 10.1007/s00709-005-0112-8
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase, peroxidase, and germin-like protein activity in plasma membranes and apoplast of maize roots

Abstract: The analysis of plasma membranes from maize roots by native gel electrophoresis revealed the existence of Mn-containing 120 kDa and CuZn-containing 70, 40, and 15 kDa superoxide dismutase (SOD) isoform activities. Isoelectric focusing of the plasma membranes differentiated anionic SOD isoforms with a pI of about 5 and cationic SOD isoforms at pI 8.6. Solubilization of the plasma membrane proteins further separated the cationic SOD into pI 8.6, 8.2, 8.4, and 7.2 isoforms. Double staining for both SOD and peroxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…It has been known for quite some time that several germins and GLPs act as OXOs (Neutelings et al, 1998) or superoxide dismutases (Carter and Thornburg, 2003;Christensen et al, 2004;Kukavica et al, 2005) and produce reactive oxygen species that provide protection against microbial infection (Hurkman and Tanaka, 1996;Carter and Thornburg, 2003). In a detailed study of the in planta role of OXO in Lolium perenne, Le Deunff et al (2004) concluded that germin OXOs might be instrumental during critical events in the life of plants, such as cutting and senescence by initiating H 2 O 2 -mediated defenses against pathogens and foraging animals.…”
Section: Resultsmentioning
confidence: 99%
“…It has been known for quite some time that several germins and GLPs act as OXOs (Neutelings et al, 1998) or superoxide dismutases (Carter and Thornburg, 2003;Christensen et al, 2004;Kukavica et al, 2005) and produce reactive oxygen species that provide protection against microbial infection (Hurkman and Tanaka, 1996;Carter and Thornburg, 2003). In a detailed study of the in planta role of OXO in Lolium perenne, Le Deunff et al (2004) concluded that germin OXOs might be instrumental during critical events in the life of plants, such as cutting and senescence by initiating H 2 O 2 -mediated defenses against pathogens and foraging animals.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the apoplast space seems to be more complex than we could expect because it contains other elements such as SOD (Streller et al 1997;Vanacker et al 1998;Kukavica et al 2005), the antioxidant glutathione (GSH) (Vanacker et al 1999;Pignocchi and Foyer 2003), and nitric oxide (St€ ohr and Ullrich 2002; Bethke et al 2004). Thus, the SOD must regulate the H 2 O 2 production during the dismutation of O 2…”
Section: Plasma Membranementioning
confidence: 96%
“…The mRNA level specific to MtGlp1 from M. truncatula was strongly induced in the roots as well as root cultures colonized by Glomus intraradices, an arbuscular mycorrhiza (Doll et al 2003). Among the Poaceae family, the plasma membranes of maize roots possess a germin-like protein of 120 kDa (Kukavica et al 2005) whereas another GLP from rice (OsGLP1) did not show any gene-specific transcript in root tissue . Gucciardo et al (2007) reported a SOD activity in a protein having similar electrophoretic mobility to that of PsGER1 protein from pea (Pisum sativum) roots.…”
Section: Expression and Biological Functions Of Glps In Root Tissuesmentioning
confidence: 96%